Application Analysis Technique For Order Preference By Simillarity To Ideal Solution In the Electoral Power Energy Saving Light Bulbs For Home Appliances: Application Analysis Technique For Order Preference By Simillarity To Ideal Solution In the Electoral Power Energy Saving Light Bulbs For Home Appliances - Agustina Simangungsong (Institute of Computer Science (IOCS), 2020)
In the election of Light Bulbs these users are often confused with the choice of Light Bulbs are so many in the market, ranging in terms of brand, type, quality, prices continue to compete and with other advantages in the offer often leads to user confusion to get energy-saving Light Bulbs at an affordable price and with quality terbaik.Permasalahan do not stop there alone at the time of placement of the ball lamp in each room of the house too often mendapatakan problem. The problem is that often caused the discrepancy, it happens at the time of Bulb has been placed. Watt capacity existing on Light Bulbs often do not match the size of the room resulting in less than optimal lighting, watt capacity or large power consumption occasionally does not guarantee to be able to get information that bagus.Oleh because it takes a decision support system that can perform calculations for the value can help the user determine the desired Bulb properly and appropriately in accordance with needs. This decision support system implementing the method of technique for order preference by simillarity to ideal solution (TOPSIS), a method that can memeberikan and perangkingan weighting for each criteria. With the method technique for order preference by simillarity to ideal solution (TOPSIS), the author makes a system which is expected eventually to help make decisions in the selection of electrical Light Bulbs.